Manipulação de carboidratos associado a treinamento físico contínuo e intermitente em indivíduos com excesso de peso - Machado, Ana Carolina Santos Barbosa (2016)
INTRODUCTION The handling of the carbohydrate diet associated with physical exercise regularly bring benefits on body composition, cardiometabolic capacity and physical fitness in individuals with overweight. AIM 1 To compare changes in body composition and physical fitness in overweight and obese undergoing a 12-week weight loss program. METHODS 1 Study participants were 33 adults overweight and sedentary undergoing intermittent exercise and continuous exercise of semi-supervised way for 12 weeks. anthropometric measurements were measured (body mass, waist and hip circumferences, weight in fat and fat percentage) and physical tests (neuromuscular and cardiovascular). We used two-way ANOVA for data analysis, and 5% significance level. RESULTS 1 There was reduced body weight, abdomen and hip circumferences, fat percentage, weight in fat and weight in lean mass (p <0.05). On the parameters of physical fitness, there was an improvement of lower limb strength, agility, speed and cardiorespiratory capacity of individuals, however, with moderate to high effect size in intermittent exercise group for agility and a 6-minute running test (p < 0.05). There was no interaction between the type of exercise and physical fitness parameters (p> 0.05). CONCLUSION 1 Regular physical exercise in obese cause improvements in body composition and physical fitness regardless of the type of exercise. However, it seems that intermittent exercise has a greater clinical effect. AIM 2 To evaluate the effectiveness of reducing carbohydrate on body composition and cardiometabolic markers of sedentary obese women. METODOLODIA 2 study included 24 obese women and 8 consuming diets with adequate carbohydrate (A-CHO) and 16 consuming diets with reduced carbohydrate (R-CHO) performing continuous exercise semi-supervised for 12 weeks. anthropometric measurements were measured (body mass, waist and hip circumferences, weight in fat and fat percentage), biochemical (cholesterol and its fractions, ALT, AST, uric acid, urea, glucose). We used two-way ANOVA for data analysis, and 5% significance level. RESULTS 2 There was a reduction of body weight, abdomen and hip circumferences, fat percentage, weight in fat and weight in lean mass over time (p <0.05). About cardiometabolic parameters, carbohydrate diet manipulations responded similarly over time over time in the lipid profile, glycemia and AST (P <0.05). When evaluating the interaction of both diets with anthropometric and crdiometabólicos parameters, there was no interaction (p> 0.05). CONCLUSION 2 The improved food profile associated with regular physical exercise in obese cause improvements in body composition, cardiometabolic profile regardless of the type of dietary carbohydrate